Imaginarium religijne w reklamie komercyjnej i społecznej na przykładzie wykorzystania wizerunków Ostatniej Wieczerzy oraz krzyża - Draguła, Andrzej (Poznańskie Spotkania Językoznawcze, 2015)
Contemporary advertising, both commercial and social, appeals increasingly to religious symbolism as a rhetorical argument. Communicative as well as persuasive effectiveness of advertising depends indeed on the appropriate denotation and connotation of the iconography used in visual advertisements. Religious, and particularly Christian, symbolism is generally clear to the addressees in our culture. This paper aims to answer the question of the consequences which the cultural reinterpretation of Christian imagery in visual advertising brings. The author argues that this process results in a “semantic shift” involving the expansion of the original meanings. On the one hand, Christian iconography loses some of its genetic sacredness; on the other hand, it sacralizes the new reality which is being advertised. The author proves his thesis by means of pointing to the reinterpretation of two established Christian images, i.e. the Last Supper and the Cross.